Sex Determination Based on Morphological and Morpho-metric Study of Clavicular Rhomboid Fossa in Saurashtra Region, Gujarat - Trangadia, Mahesh M; Gupta, B D (Journal of Indian Academy of Forensic Medicine, 2020)
The correct determination of the sex of a person are critical requirement in physical anthropology and one of the essential steps in personal identification of an individual from the skeletal remains. The present study was conducted prospectively on 200 pairs of the clavicles which were obtained from the dead bodies brought for post mortem examination during the period of January 2014 to December 2014 in Forensic Medicine department, M. P. Shah Govt. Medical College, Jamnagar, Gujarat. The results indicate that Incidence of rhomboid fossa on right side of clavicle in males and females was statistically not significant (p>0.05). While the greater difference in fossa expression was noticed between male and female clavicles of left side, which had statistical significance (p<0.01). Elevated rhomboid fossa is more frequent in both the sexes, followed by flat nature and then depressed nature. The mean length of rhomboid fossa of right side clavicle was 20.56mm±5.99 in male and 15.28mm±4.89 in female, while on left side, the length was 19.24mm±5.57 and 15.97mm±5.88 respectively for males and females. The mean breadth of rhomboid fossa of right side clavicle was 10.71mm±3.51 in male and 8.35mm±2.73 in female, while on left side breadth was 9.58mm±2.83 and 8.13mm±2.89 respectively for male and female. It has been concluded that the length and breadth of rhomboid fossa of clavicle as a single parameter can’t establish the sex of each clavicle in study population.